The Effectiveness of Group Counseling using Role Reversal Technique to Improve Social Skills Among Students in Inclusive Schools - Ratih Christiana; Dahlia Novarianing Asri (Journal An-Nafs: Kajian Penelitian Psikologi, 2026)
This study aimed to examine the effectiveness of group counseling using the role reversal technique in improving students’ social skills. This study was motivated by students’ low levels of social skills, particularly in cooperation, empathy, and interpersonal communication. The study employed a quantitative pre-experimental approach using a one-group pretest–posttest design. The participants consisted of eight junior high school students with low levels of social skills who participated in the study. Data were collected using a validated and reliable social skills questionnaire measuring empathy, communication, openness, helping behavior, and self-understanding. The data were analyzeda paired-samples t-test. The results showed a significant improvement in participants’ social skills following group counseling using the role reversal technique (t(7) = 12.396, p < .001). The finding suggest that group counseling using the role reversal technique is effective in improving students’ social skills.